Distinct genes and pathways associated with transcriptome differences in early cardiac development between fast- and slow-growing broilers - Zhang, Jibin (PLoS One, 2018)
Modern fast-growing broilers are susceptible to cardiac dysfunctions because their relatively small hearts cannot adequately meet the increased need of pumping blood through a large body mass. To improve cardiac health in broilers through breeding, we need to identify the genes and pathways that contribute to imbalanced cardiac development and occurrence of heart dysfunction. Two broiler lines–Ross 708 and Illinois–were included in this study as models of modern fast-growing and heritage slow-growing broilers, respectively. The left ventricular transcriptome were compared between the two broiler lines at day 6 and 21 post hatch through RNA-seq analysis to identify genes and pathways regulating compromised cardiac development in modern broilers. Number of differentially expressed genes (DEGs, p<0.05) between the two broiler lines increased from 321 at day 6 to 819 at day 21. As the birds grew, Ross broilers showed more DEGs (n = 1879) than Illinois broilers (n = 1117). Both broilers showed significant change of muscle related genes and immune genes, but Ross broilers showed remarkable change of expression of several lipid transporter genes including APOA4, APOB, APOH, FABP4 and RBP7. Ingenuity pathway analysis (IPA) suggested that increased cell apoptosis and inhibited cell cycle due to increased lipid accumulation, oxidative stress and endoplasmic reticulum stress may be related to the increased cardiac dysfunctions in fast-growing broilers. Cell cycle regulatory pathways like “Mitotic Roles of Polo-like Kinases” are ranked as the top changed pathways related to the cell apoptosis. These findings provide further insight into the cardiac dysfunction in modern broilers and also potential targets for improvement of their cardiac health through breeding.